GENE POLYMORPHISMS OF ENDOTHELIAL DYSFUNCTION, COACTIVATORS OF MITOCHONDRIAL BIOGENESIS AND PLASMINOGEN/PLASMIN SYSTEM IN THE DEVELOPMENT OF CARDIOVASCULAR EVENTS IN RHEUMATOID ARTHRITIS - A. V. Shevchenko; V. F. Prokofyev; M. O. Korolev; V. O. Omelchenko; V. I. Konenkov (Научно-практическая ревматология, 2018)
Cardiovascular catastrophes are the most common cause of death in patients with rheumatoid arthritis (RA). At the same time, the mechanism of progression of atherosclerotic lesions in the vascular bed in RA, including genetic factors, remains a matter of debate. Objective: to analyze the associativity of polymorphism of the NOS3, PPARG γ , PPARGC1А, PPARGC1B and PAI-1 gene with a high/low cardiovascular risk in patients with RA.Subjects and methods. The investigation enrolled 73 patients with RA. Of them, 67.1% were at high cardiovascular risk. Ultrasonography of the brachiocephalic arteries with determination of intima-media thickness (IMT) was used as a surrogate marker for cardiovascular risk. A comparison was carried out taking into account the relevant standards. The IMT value exceeding the above parameters was regarded as the sign of a high cardiovascular risk. Single nucleotide polymorphisms in the NOS3 (rs2070744), PPARG2 (rs1801282), and PPARGC1A (rs8192678), PPARGC1B (rs7732671), and PAI1 (rs1799889) genes were investigated by a real-time polymerase chain reaction assay using the intercalating dye SYBR Green I according to the instructions of the manufacturer («Litech», Russia).Results and discussion. The frequencies of the NOS3 -786ТТ genotypes significantly differed in patients at different cardiovascular risks. Complex genotypes, the frequency of which was prevalent in the low cardiovascular risk group, were identified. At the same time, all genotypes contained the homozygous NOS3 -786ТТ genotype and the genes that were able to regulate its expression. The greatest differences between the analyzed groups were present in the complexes of NOS3-786TT:PPARGC1B 203AlaAla and NOS3 -786TT:PPARGC1B 203AlaAla:12 PPARG ProPro.Conclusion. Our analyzed gene polymorphic positions can concurrently affect cardiovascular risk in patients with RA.